Antiplatelet Therapy for Carotid Artery Stenting - Enomoto, Yukiko (S. Karger AG, 2013)
Carotid artery stenting (CAS) is less invasive and has a lower incidence of systemic complications such as myocardial infarction compared with carotid endarterectomy. However, CAS is known to have a high incidence of ischemic complications due to distal thromboembolism. Progress has been made in the development of various distal protection devices and protection methods aimed at preventing thromboembolism. Similar to these methods, perioperative antiplatelet therapy is also able to play a very important role in the prevention of ischemic events. Dual antiplatelet therapy has become standard for perioperative management of CAS.